AB0199 IGG Subclasses of Autoantibodies Directed against the Angiotensin Receptor Type 1 and the Endothelin Receptor Type A and their Clinical Relevance. (10th June 2014) - Guenther, J.; Kill, A.; Becker, M.O.; Siegert, E.; Heidecke, H.; Riemekasten, G.
Abstract : Background: IgG4-related diseases are often characterized by a generalized inflammatory fibrosis which is also present in patients suffering from systemic sclerosis (SSc). Recent findings indicate the importance of autoantibodies (Aabs) against the angiotensin II receptor type 1 (AT1R) and the endothelin receptor type A (ETAR) in the pathogenesis of SSc. Objectives: Aim of the study was to analyse associations between the serum levels of anti-AT1R/ETAR IgG sublasses of SSc patients and their clinical features in order to determine a possible role of certain subclasses as markers for disease manifestations. Methods: Sera from 91 SSc patients, 59 patients suffering from systemic lupus erythematosus (SLE), and 199 healthy donors were analysed for the levels of anti-AT1R and anti-ETAR Aabs as well as for the different anti-AT1R and anti-ETAR IgG subclasses by ELISA. The results were associated with clinical manifestations using Mann-Whitney test and correlated with the time since onset of disease manifestations by Spearman correlation test. Results: IgG3 followed by IgG1 was found to show highest anti-AT1R/ETAR Aab levels in all analyzed groups, in which SSc patients as well as SLE patients had higher IgG1 and IgG3 anti-AT1R/ETAR Aab levels as compared to healthy donors. Comparing SLE and SSc patients IgG1 and IgG3 showed a bit higher anti-AT1R/ETAR Aab level in SLE. Within the SSc group patients with diffuse SSc had higher anti-AT1R/ETAR IgG3 levels as compared to those with limited disease or overlap forms. Correlation analysis with SSc-related clinical manifestations revealed that levels of anti-AT1R/ETAR IgG3 negatively correlated with time since onset of Raynaud's phenomenon, and with time since first detection of pulmonary arterial hypertension. Of note, there were negative correlations between levels of anti-AT1R/ETAR IgG3 levels and diffusion capacity of the lung for carbon monoxide (DLCO) as well as between anti-AT1R/ETAR IgG3 levels and forced vital capacity (FVC) values (p=0.02/0.07 and p=0.01/0.03, respectively). Conclusions: Interestingly, not IgG4 but IgG3 showed highest anti-AT1R/ETAR Aab levels when compared to other IgG subclasses. However, in SSc patients, anti-AT1R/ETAR IgG3 levels are strongly correlated to certain disease manifestations, whereby high anti-AT1R/ETAR IgG3 levels are associated with low DLCO and FVC indicating deterioration of lung function. According to these findings high anti-AT1R/ETAR IgG3 levels could predict for lung function deterioration and represent a new marker for SSc complications. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3699